Sustentabilidad de la producción apícola del Municipio de Altamirano, Chiapas, México - Jiménez Hernández, Ela (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The bees are pollinating insects that play a fundamental role in Food production, carrying out 80% pollination in 250 thousand plant species, in which bees carry out 75% pollination, producing an estimated anual value between 235 and 577 billion dollars. Beekeeping is the activity that is dedicated to the exploitation of bees and BPP to improve the management and care of bees, this in order to conserve Beekeeping resources. The objective of this research is to carry out an evaluation of Beekeeping base don the implementation of Good Livestock Practices in Honey production, according to the beekeepers of the municipality of Altamirano, Chiapas, in the year 2020, using the Management Systems Evaluation Framework incorporating Sustainability Indicators, which describes the characteristics of the management system in accordance with the BPP, the method was developed to determine the priority in independent variables: The case of tourist competitiveness “to generate infomation on critical points and measurement of indicators base on the interview, mind map, bibliographic review (theoretical analysis) and applied models. The tool in this case for the collection of the information was a questionnaire that was applied to the beekeepers of the region to assess each indicator, a radial graph was elaborated to present the panorama and based on the results that show that, the Beekeeping activity is very unsustainable in the region, since beekeepers who do practice BPP show declines in all three dimesions, economic, and social, while beekeepers who do not practice BPP show unsustainability in the social dimension. In addition, it was shown that the economic dimension is the one with the highest level of Sustainability, followed by the environmental and social.

Las abejas son insectos polinizadores que juegan un papel fundamental para la producción de alimentos, realizando el 80% de polinización en 250 mil especies de plantas, en el cual las abejas realizan el 75% de polinización, produciendo un valor anual estimado entre 235 y 577 mil millones de dólares (Heiblum, 2019). La apicultura es la actividad que se dedica a la explotación de las abejas y las Buenas Prácticas Pecuarias en la producción de miel (BPPPM) a mejorar el manejo y cuidado de las abejas, esto con el fin de conservar los recursos apícolas. El objetivo de la presente investigación es realizar una evaluación de la sustentabilidad de la producción apícola a partir de la implementación de las BPPPM, de acuerdo con los apicultores del municipio de Altamirano, Chiapas, en el año de 2020, utilizando el Marco de Evaluación de Sistemas de Manejo incorporando Indicadores de Sustentabilidad (MESMIS), en el que se describieron las características del sistema de manejo de acuerdo con BPPPM, se desarrolló el método para determinar prioridad en variables independientes, para generar información de los punto críticos y medición de los indicadores con base a la entrevista, mapa mental, revisión bibliográfica (análisis teóricos) y modelos aplicados. El instrumento en este caso para la recolección de la información fue un cuestionario que se aplicó a los apicultores de la región para valorar cada indicador y con base a los resultados muestran que, la actividad apícola es muy poco sustentable en la región, puesto que los apicultores que si practican las BPPPM, presentan decadencias en las tres dimensiones, económica, ambiental y social, mientras que los apicultores que no practican las BPP presenta una falta de sustentabilidad en la dimensión social, la dimensión económica es la que mayor nivel de sustentabilidad tiene, seguida de la ambiental y social.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias del Desarrollo Regional
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2022-0096; Sistema apícola; MESMIS; Insustentabilidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6635